2009
DOI: 10.1016/j.eururo.2008.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Deprivation Therapy for the Treatment of Prostate Cancer: Consider Both Benefits and Risks

Abstract: Context-Androgen deprivation therapy (ADT) is increasingly used for the treatment of prostate cancer (PCa), even in clinical settings in which there is no evidence-based proof of prolonged overall survival (OS). ADT, however, may be associated with numerous side effects, including an increased therapy-related cardiovascular mortality.Objective-To discuss different clinical settings in which ADT is currently used and to critically weigh the benefits of ADT against its possible side effects.Evidence acquisition-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
83
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(85 citation statements)
references
References 105 publications
(135 reference statements)
0
83
0
2
Order By: Relevance
“…Over the past decade, increasing evidence suggested that ADT, which leads to castrate testosterone level, is associated with numerous side effects, such as osteoporosis, obesity, sarcopenia, lipid alterations, insulin resistance and increased risk for diabetes and cardiovascular morbidity. 13 Moreover, serum PSA, which is widely used for early detection and monitoring the treatment response of PCa, is strongly androgen-dependent. Therefore, studies investigating the timing and extent of testosterone recovery after ADT cessation in PCa patients should focus on two crucial issues: first, time of testosterone recovery to supracastrate level, and second, time of testosterone recovery to normal level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decade, increasing evidence suggested that ADT, which leads to castrate testosterone level, is associated with numerous side effects, such as osteoporosis, obesity, sarcopenia, lipid alterations, insulin resistance and increased risk for diabetes and cardiovascular morbidity. 13 Moreover, serum PSA, which is widely used for early detection and monitoring the treatment response of PCa, is strongly androgen-dependent. Therefore, studies investigating the timing and extent of testosterone recovery after ADT cessation in PCa patients should focus on two crucial issues: first, time of testosterone recovery to supracastrate level, and second, time of testosterone recovery to normal level.…”
Section: Discussionmentioning
confidence: 99%
“…After testosterone recovered to normal level, the side effects of ADT would disappear completely. 13,14 Time of testosterone recovery to supracastrate level after ADT has been investigated in previous studies. In a randomized clinical trial using intermittent hormonal therapy for PCa patients with increasing PSA after definitive local treatment, Gulley et al 6 found that after 6 months of ADT, more than 90% patients achieved supracastrate serum testosterone level by 18 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-eight reviews (Ahles & Saykin 2007;Artherholt & Fann 2012;Beauchet 2006;Biegler et al 2009;Chen & Petrylak 2004;Chism & Kunkel 2009;Droz et al 2010;Falci et al 2009;Green et al 2005;Grossmann & Zajac 2011;Gruca et al 2012;Harrington et al 2010;Holzbeierlein 2006;Isbarn et al 2009;Jamadar et al 2012;Janelsins et al 2011;Mitsiades et al 2008;Mohile et al 2009;Mottet et al 2006;Nelson et al 2008;Scherr & Pitts 2003;Sharifi 2005;Trost et al 2013;Tombal 2009;Wefel et al 2004;Wright et al 2006;Ziółkowska et al 2012) described twenty primary studies (Alibhai et al 2010;Almeida et al 2004;Beer et al 2006;Beer et al 2004;Bloomfield & Shilling 2004;Bussiere et al 2005;Cherrier et al 2003;Cherrier et al 2009;DiBlasio et al 2008;Green et al 2002;Green et al 2004;Jenkins et al 2005;Joly et al 2006;Mohile et al 2010;…”
Section: Review Characteristicsunclassified
“…[7][8][9] Although ADT offers important clinical benefits, it is associated with a variety of complications such as hot flushes, anaemia, sexual dysfunction, changing body composition, osteoporosis and fractures, and increased risk for diabetes and cardiovascular diseases. [10][11][12] Some of the complications have negative effects on quality of life assessments, while others may induce serious problems including myocardial infarction and sudden cardiac death. 13 A longterm study revealed that 53% of the deaths were not attributable to prostate cancer.…”
Section: Introductionmentioning
confidence: 99%